The bush-cricket Isophya kraussii (Orthoptera: Phaneropteridae): bioacoustics, distribution and description of a new subspecies from Romania - Iorgu, Ionuţ Ştefan; Heller, Klaus-Gerhard (Zootaxa, 2013)
Isophya kraussii Brunner von Wattenwyl, 1878, one of the widest spread bush–crickets within this genus, is confirmed to be present east of the Carpathian Mountains. Based on acoustic analysis and morphological characters, the populations from NE Romania are considered to belong to a different subspecies, I. kraussii moldavica ssp. n. A map with distribution of both subspecies is presented.